Pengembangan Modul Ajar Sistem Persamaan Linear Berbasis Proyek Terkait Kemampuan Pemecahan Masalah - Leni Apriyanti; Yayu Laila Sulastri; Deti Ahmatika; Dini Cahya Aprilani; Usep Kosasih (SAP (Susunan Artikel Pendidikan), 2023)
This research was moved by the lack of learning tools that suit students' needs and the low problem solving abilities of students in linear equation systems material. This is the main justification behind the need to develop a teaching module for systems of linear equations that is related to problem solving abilities. This research aims to determine the validity, practicality and effectiveness of the teaching modules developed. This research was carried out in class A-1 of the Nusantara Islamic University Mathematics Education Study Program for the 2022/2023 academic year. This study expects to decide the validity, practicality, and effectiveness of the created educating modules. This examination technique is called plan research with the Plomp model. The information sources in this study are expert validators and students. The data collection instruments used were expert validation sheets, practicality questionnaire sheets, and formative assessment sheets consisting of problem-solving ability tests, affective questionnaires, observations in the affective domain and the psychomotor domain. This information is analysed using percentages outlined based on qualifications. Based on the tests carried out, it can be concluded that the teaching module developed is valid, practical and very effective.